Excess charge driven dissociative hydrogen adsorption on Ti2O4−. Issue 34 (18th August 2017) - Song, Xiaowei; Fagiani, Matias R.; Debnath, Sreekanta; Gao, Min; Maeda, Satoshi; Taketsugu, Tetsuya; Gewinner, Sandy; Schöllkopf, Wieland; Asmis, Knut R.; Lyalin, Andrey
Abstract : The mechanism of dissociative D2 adsorption on Ti2 O4 − is studied using infrared photodissociation spectroscopy in combination with density functional theory calculations. Abstract : The mechanism of dissociative D2 adsorption on Ti2 O4 −, which serves as a model for an oxygen vacancy on a titania surface, is studied using infrared photodissociation spectroscopy in combination with density functional theory calculations and a recently developed single-component artificial force induced reaction method. Ti2 O4 − readily reacts with D2 under multiple collision conditions in a gas-filled ion trap held at 16 K forming a global minimum-energy structure (DO–Ti–(O)2 –Ti(D)–O) − . The highly exergonic reaction proceeds quasi barrier-free via several intermediate species, involving heterolytic D2 -bond cleavage followed by D-atom migration. We show that, compared to neutral Ti2 O4, the excess negative charge in Ti2 O4 − is responsible for the substantial lowering of the D2 dissociation barrier, but does not affect the molecular D2 adsorption energy in the initial physisorption step.